Self versus employees’ Appraisal of managers’ emotional intelligence: the case of Gweru and Kwekwe city councils, Midlands Province, Zimbabwe - Chirasha, Vonai; Chipunza, C.; Dzimbiri, L. (Midlands State University, 2016)
Emotional Intelligence has become increasingly popular as a management tool for boosting performance at work. Despite this popularity, there is no sustained research in Zimbabwe that substantiates the efficacy of emotional intelligence especially within municipality environments. The objective of the study was to compare levels of emotional intelligence among City Council Managers from two cities in Zimbabwe. Using purposive and stratified sampling techniques, 32 managers and 400 subordinates were respectively selected to participate in the study. Goleman‘s Emotional Competency Inventory (ECI 2.0) which measures self and employees’ appraisal of managers was used to collect data. Interviews were later used to corroborate data from the survey. The results, analysed using t - test for independent samples as well content analysis, showed differences in the self-ratings by city council managers compared to employees’ ratings of the same managers. The assumption that self rating and others’ rating can-not be same was validated.